Salud pública - Romero Rojas, Jairo Alberto (Universidad Escuela Colombiana de Ingeniería Julio Garavito, 2020)
Como lo define la Organización Mundial de la Salud (OMS), la aspiración de cualquier ciudadano es tener siempre salud: estado de completo bienestar físico, mental y moral.

As defined by the World Health Organization (WHO), it is the aspiration of every citizen to have health: a state of complete physical, mental and moral well-being, mental and moral well-being.

Como lo define la Organización Mundial de la Salud (OMS), la aspiración de cualquier ciudadano es tener siempre salud: estado de completo bienestar físico, mental y moral. El problema actual, creado por la contaminación con la covid-19, despierta y revive la importancia de tener salud, y demuestra que nos hemos olvidado de hacer lo necesario para satisfacer óptimamente el objetivo social primordial de brindar salud a todo ciudadano.

As defined by the World Health Organization (WHO), the aspiration of any citizen is to always be healthy: a state of complete physical, mental and moral well-being. The current problem, created by covid-19 contamination, awakens and revives the importance of having health, and shows that we have forgotten to do what is necessary to optimally satisfy the primary social objective of providing health to every citizen.
Keywords: Salud pública; Public health; Pandemia de COVID-19, 2020-; COVID-19 Pandemic, 2020-; Cuarentena; Quarantine